A DEVELOPMENT ONLINE LEARNING MODEL BASED ON STEM EDUCATION TO ENHANCE CREATIVE THINKING FOR UNDERGRADUATE STUDENTS IN INSTITUTE OF PHYSICAL EDUCATION - Kingpoum, Peerasak; Ruangsuwan, Chaiyot (Academic Journal of Thailand National Sports University, 2022)
The research, therefore, aimed to (1) Development online Learning Model Based on STEM Education to Enhance Creative Thinking for Undergraduate Students in the Institute of Physical Education and (2) to study the results of implementing the instructional activities developed with the sample of undergraduate students at the Institute of Physical Education. The sample group was 30 undergraduates who enrolled for 6 weeks, 3 hours each, in the second semester of the academic year 2017, majoring in Exercise Science, and the sample of the undergraduates were selected by simple random sampling method from the total population of 30 in the institute of physical education Mahasarakham campus. All students took the course for the first time. Research instruments included (1) the developed online Learning Model Based on STEM Education instructional activity, (1) Learning Management System (LMS), (2) the learning achievement test, (3) the creative thinking test, (5) Behavior Observation form for lecturer. The collected data were analyzed using percentage, mean, standard deviation; and the dependent t - test was employed. The findings showed that: there are four components in the model of STEM Education online learning namely (1) principles, (2) objectives, (3) procedures and instructional activities, and (4) measurement and evaluation. The instructional processes are divided into 3 phases, namely, (1) preparation, (2) online learning management, and (3) measurement and evaluation. The experts assessed the developed model at the most appropriate level. The experimental group of students showed gains in learning achievement and creative thinking as a whole and in each subscale from before learning with the developed model at the .01 level of significance, the students showed their opinions about Refection learning with the developed model at the appropriate level.